Plan estratégico para la empresa distribuidora APRONAM S.A. del cantón Chone - Obando Arias, Nayeli Dayanna (2024)
The present study was conducted with the aim of developing a strategic plan for APRONAM S.A., a distributor in Chone canton. Within this context, the company's internal and external factors were determined by conducting an interview with its manager. Subsequently, the degree of competitive capacity was measured, and a value chain analysis was carried out. The PESTEL factors were reviewed, and the competitive level was analyzed using Porter’s five forces. Strategies were formulated by integrating the internal and external analysis of the organization, which were evaluated through the EFI and EFE matrices. The SWOT matrix allowed for a situational diagnosis of the company, followed by the formulation of SMART objectives that were related to the PEYEA matrix in the formulation of competitive strategies. Finally, an action plan was designed to achieve the established strategies by implementing a 5W+2H scheme, aimed at promoting the competitive growth of APRONAM S.A. The results show that the company possesses great versatility to adapt to needs, apply discounts, and segment customers, positioning it well to seize opportunities and minimize threats in its environment. In conclusion, APRONAM S.A. is demonstrated to be a dynamic and strategic entity focused on product quality, consolidating itself as a relevant player in the food market with promising business prospects for the future.